Coping with Community Violence: Perspectives of African American Young Adult Men and Hispanic/Latino Young Adult Men - Byrd, Kourtney A. D. (Journal of interpersonal violence, 2024)
Further study is needed regarding the intersection of community violence exposure, coping strategies, and health behaviors among young adult African American men and Hispanic/Latino men. This study did so in Lake County, Indiana, which contains multiple areas with disproportionate prevalence of violence relative to population size. Approximately 22 miles from Chicago, Lake County includes noteworthy mid-sized cities such as Gary, Hammond, and East Chicago. This study explored the perceptions of African American men and Hispanic/Latino men ages 18 to 25 regarding coping strategies and both healthy and health risk behaviors after directly witnessing or indirectly experiencing a violent act or event. We used aspects of social cognitive theory to design this community-based participatory research study. Thirteen males who self-identified as African American, Hispanic/Latino, or both, completed 34- to 80-minute, audio-recorded phone interviews. Audio recordings were transcribed, and NVivo 12 Windows was used by the research team (primary researchers and two coders) to complete transcript analysis. Findings from this study provided insight around African American men and Hispanic/Latino men regarding (a) witnessing violence directly or indirectly experiencing violence; (b) changes in everyday life experiences; (c) coping strategies that involved socio-emotional health, spiritual health, social health, and risky health behaviors; (d) rationales for not asking for help; (e) observations of significant others’ coping; (f) what to do differently in the future; (g) beliefs about mentors; and (h) beliefs about mental health providers. Delving into participants’ experiences revealed that African American men and Hispanic/Latino men in Lake County, Indiana chose to adopt a range of health risk and health positive strategies after directly witnessing or indirectly experiencing violence. Becoming knowledgeable about African American men’s and Hispanic/Latino men’s diverse coping strategies and health behaviors may help inform the community about how best to cocreate spaces that aim to alleviate the traumatic experience of having directly or indirectly experienced community violence.